ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UPAYA TINDAKAN TAX AVOIDANCE (Students' Journal of Accounting and Banking, 2015)
This study aimed to analyze the influence of Institutional Ownership, Independent Commissioner Board,and Audit Committee, Against Tax Avoidance. In the manufacturing sector the basic chemical industry in Indonesia Stock Exchange. The sample in this study was obtained by using purposive sampling method. Based on the criteria that is the importance of the 76 companies in the research samples with the period 2010-2013. This research was conducted by using multiple linear regression analysis. The results showed that the significant positive effect of institutional ownership and audit quality are not significant positive effect on tax avoidance. While the negative influence of independent board and audit committee is not significant effect on tax avoidance.Keywords: Institutional Ownership, Independent Commissioner Board, Committee Audt, and Tax Avoidance